Social media policy in Egypt: case studies of three ministries - Kenawy, Gehad Soliman (AUC Knowledge Fountain, 2015)
The use of social media tools in Egyptian government, while still relatively new, is gaining acceptance at all levels of government which is widely reflected in the number of social media pages for Egyptian ministries. By logging on Facebook or Twitter you can follow most of Egyptian ministries updated releases and news. Yet, it is still not clear how Egyptian government is regulating public employees' use of such interactive platforms. The purpose of this study is to answer the main research questions: What are the key elements of a social media policy? How Egyptian ministries are using social media? How Egyptian ministries are managing their social media pages? What challenges are Egyptian ministries encountering as they use social media? To achieve this purpose, the methodology adopted in this study include a review of literature, analysis of existing social media policies in different countries, and interviews with social media officials in a purposive non- random sample of Egyptian Ministries to examine their policies regarding social media use. The sample includes the Ministry of Finance, the Ministry of Planning, Monitoring and Administrative Reform, and the Ministry of Supply and Internal Trade, as they represent Egyptian ministries from different levels; sovereign, economic and service ministries. The study findings indicate that the Egyptian government lacks having social media policies that regulate the use of social media. After interviewing social media officials in different Egyptian ministries, it has been concluded that there are no concrete written policies that monitor and regulate public employees' usage of social media. Finally, this thesis recommends a social media policy guide for Egyptian government that will assist in setting guidelines that regulate their use of social media.